2019
DOI: 10.1177/1178646919855942
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma: Role of Mitochondria N-acetylserotonin/Melatonin Ratio in Mediating Effects of miR-451 and Aryl Hydrocarbon Receptor and in Coordinating Wider Biochemical Changes

Abstract: A wide array of different factors and processes have been linked to the biochemical underpinnings of glioblastoma multiforme (GBM) and glioblastoma stem cells (GSC), with no clear framework in which these may be integrated. Consequently, treatment of GBM/GSC is generally regarded as very poor. This article provides a framework that is based on alterations in the regulation of the melatonergic pathways within mitochondria of GBM/GSC. It is proposed that the presence of high levels of mitochondria-synthesized me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 108 publications
(140 reference statements)
0
33
0
Order By: Relevance
“…In the hopes of blocking tumor growth, Franco et al [35] studied the effects of 3 mM melatonin on human GBM cells and observed a reduced expression of mitochondrial transcription factor A (TFAM), which is an essential protein that maintains mitochondrial DNA (mtDNA) integrity [65,66]. Moreover, melatonin selectively induced a surprisingly concentration-dependent increase in ROS production and delayed cell-cycle progression in GBM cancer cells as compared to the control group [35], while the presence of high levels of mitochondria-synthesized melatonin appears to be toxic for GBM and GSCs [67]. This effect of melatonin on ROS production may be due to the altered expression of respiratory chain genes, which could depend on the activity of the transcription factors TFAM, TFB1M, and TFB2M [35].…”
Section: In Vitro Evidence Of Melatonin Effects Against Glioblastomamentioning
confidence: 99%
“…In the hopes of blocking tumor growth, Franco et al [35] studied the effects of 3 mM melatonin on human GBM cells and observed a reduced expression of mitochondrial transcription factor A (TFAM), which is an essential protein that maintains mitochondrial DNA (mtDNA) integrity [65,66]. Moreover, melatonin selectively induced a surprisingly concentration-dependent increase in ROS production and delayed cell-cycle progression in GBM cancer cells as compared to the control group [35], while the presence of high levels of mitochondria-synthesized melatonin appears to be toxic for GBM and GSCs [67]. This effect of melatonin on ROS production may be due to the altered expression of respiratory chain genes, which could depend on the activity of the transcription factors TFAM, TFB1M, and TFB2M [35].…”
Section: In Vitro Evidence Of Melatonin Effects Against Glioblastomamentioning
confidence: 99%
“…Many of the changes associated with LVH are also evident in proliferative conditions, such as endometriosis and a wide array of cancers [8,9]. Recent works suggest that alterations in mitochondria functioning, particularly the regulation of the melatonergic pathways, may be a core aspect of how changes in mitochondria drive the co-ordinated pathophysiological processes underpinning these diverse medical disorders [8,9]. The current article reviews how aryl hydrocarbon receptor (AhR)-induced cytochrome P450 (CYP)1B1 suppresses mitochondria melatonin production, thereby initiating the co-ordinated cellular changes evident in LVH.…”
Section: Introductionmentioning
confidence: 99%
“…High levels of melatonin synthesis in mitochondria are very toxic to GBM/GSC; hence, some processes in GBM/GSC limit mitochondria‐synthesized melatonin. For example, aryl hydrocarbon receptor increases cytochrome P450 (CYP)1b1 in mitochondria which leads to the ‘backward’ conversion of melatonin to N‐acetylserotonin (NAS) .…”
Section: Introductionmentioning
confidence: 99%